2022
DOI: 10.2147/ijn.s379917
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dynamin-Related Protein 1 and Induction of Mitochondrial Apoptosis by Exosome-Rifampicin Nanoparticles Exerts Anti-Osteosarcoma Effect

Abstract: Purpose To investigate induction of cell death in Osteosarcoma (OS) using the anti-tuberculosis drug, rifampicin, loaded into exosomes. Patients and Methods BMSC-exosomes were isolated by ultracentrifugation and loaded ultrasonically with rifampicin. Nanoparticle exosome-rifampicin (EXO-RIF) was added to the OS cell-lines, 143B and MG63, in vitro, to observe the growth inhibitory effect. In vivo experiments were conducted by injecting fluorescently labeled EXO-RIF throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…( B ) Exogenous loading involves the loading of various cargoes, such as drugs, DNAs, ncRNAs, and proteins, into native exosomes. Methods for loading these cargoes include electroporation, sonication, co-incubation, and extrusion [ 136 , 137 , 138 , 139 , 140 , 141 ]. Endogenous loading involves the packaging of biomolecules via the modification of donor cells [ 133 , 134 , 142 , 143 , 144 , 145 ].…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…( B ) Exogenous loading involves the loading of various cargoes, such as drugs, DNAs, ncRNAs, and proteins, into native exosomes. Methods for loading these cargoes include electroporation, sonication, co-incubation, and extrusion [ 136 , 137 , 138 , 139 , 140 , 141 ]. Endogenous loading involves the packaging of biomolecules via the modification of donor cells [ 133 , 134 , 142 , 143 , 144 , 145 ].…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
“…Platelet exosomes that have been loaded with doxorubicin via electroporation decrease the proliferation of MDA-MB-231 cells by increasing the expression of BAX while decreasing the expression of BCL2 [ 140 ]. BMSC-derived exosomes that have been loaded with rifampicin via ultrasound inhibit the proliferation of osteosarcoma cells, induce G2/M arrest, and mitochondrial apoptosis [ 141 ]. In doing so, the exosomes activate dynamin-related protein 1 (Drp1) [ 141 ].…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…206,210−216 Many reports concluded that exosomes incorporating therapeutic compounds were applied for small molecule delivery. 210,217 In contrast to physical methods, gene transfection is an emerging way to load active proteins or RNA into engineered exosomes. 212 Convincing results indicate that topically applied exosomes on the skin surface do not easily diffuse through the stratum corneum.…”
Section: Microneedlesmentioning
confidence: 99%
“…For the in vivo approach, drug molecules are usually fed to donor cells to package them into exosomes for therapeutic use . Several in vitro methods, such as electroporation, incubation, sonication, transfection, extrusion, and freeze–thaw, have been developed to load drugs. , Many reports concluded that exosomes incorporating therapeutic compounds were applied for small molecule delivery. , In contrast to physical methods, gene transfection is an emerging way to load active proteins or RNA into engineered exosomes . Convincing results indicate that topically applied exosomes on the skin surface do not easily diffuse through the stratum corneum .…”
Section: Development Strategies For Drug Delivery Systems In Alopeciamentioning
confidence: 99%